Closed system behaviour of argon in osumilite records protracted high-T metamorphism within the Rogaland–Vest Agder Sector, Norway - Blereau, Eleanor; Clark, Chris; Jourdan, Fred; Johnson, Tim; Taylor, Richard; Kinny, Pete; Danišík, Martin; Hand, M.; Eroglu, Ela (WILEY, 2019)
© 2019 John Wiley & Sons Ltd